Internet connectivity disruption in Slovakia (Slovakia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Slovakia. Data sourced from IODA.
Network Disruption Incident ID: SK-2026-0005. Severity: critical. Confidence: 65%